Bilateral polysegmentary pneumonia caused by SARS-CoV-2 in a transplanted liver recipient - Roman V. Ishenko; Sergei V. Golovincki; Artur R. Akhmedianov; Sergei E. Voskanyan; Ilya Yu. Kolyshev (Клиническая практика, 2020)
Background. In December 2019, the humanity met a previously unknown infectious disease (COVID-19) caused by a new coronavirus called SARS-CoV-2. An important role in the treatment of COVID-19 belongs to anti-inflammatory and immunosuppressive drugs. In this regard, the cases of the disease in patients undergoing long-term immunosuppressive therapy, for example, organ transplant recipients, are of particular interest. We present our clinical observation of COVID-19 in a liver recipient patient, which, apparently, is the first in the Russian Federation.